PENGARUH PENGGUNAAN MEDIA PRESENTASI INTERAKTIF TERHADAP KEMAMPUAN PEMAHAMAN MEMBACA SISWA SEKOLAH DASAR - Lady Lailatun Nabila; Ahmad Nurefendi Fradana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning in the digital era requires innovative approaches to improve students' reading comprehension. This study aims to explore the effect of interactive presentation media on the reading comprehension ability of grade 4B students at SDN Lemah Putro 1. The research method used was experimental with a one group pretest-posttest design. Data were collected through pretest and posttest tests, and analyzed using paired samples T-test. The results showed that the use of interactive presentation media significantly improved students' reading comprehension skills. Before the treatment, the average pretest score was 70.68, while after the treatment, the average posttest score increased to 90.91, with an increase of 20.23%. The paired samples T-test results also showed significance (p < 0.05), confirming the positive effect of interactive presentation media on students' reading comprehension skills. The findings suggest that interactive presentation media can be an effective tool in improving students' reading comprehension in the digital era. The implication of this study is the importance of technology integration in learning to facilitate an engaging and effective learning experience. It is hoped that this research can contribute to the development of innovative and effective learning strategies in improving students' reading comprehension skills in primary schools.